Preparation and Performance of Biomimetic Zebra-Striped Wood-Based Photothermal Evaporative Materials - Zebin Zhao; Wenxuan Wang; Zhichen Ba; Yuze Zhang; Hongbo Xu; Daxin Liang (Biomimetics)
An efficient solar water evaporator is an important strategy for addressing the problem of water shortage. Constructing high-performance solar interfacial evaporators through bionic design has become a crucial approach for performance enhancement. Through the study of zebra patterns, it has been found that the black-and-white alternating patterns generate vortices on the surface of the zebra’s skin, thereby reducing the temperature. By utilizing the vortices brought about by the temperature difference, the design of a solar water evaporator is created based on the bionic zebra pattern, so as to improve its water evaporation performance. In this work, green and sustainable wood is used as the base of the evaporator, and the bionic design of zebra stripes is adopted. Meanwhile, the following research is conducted: The wood is cut into thin slices with dimensions of 30 × 30 × 5 mm3, and a delignification treatment is performed. Tannic acid-Fe ions are used as the photothermal material for functionalization. A series of stable patterned water evaporators based on delignification wood loaded with tannic acid-Fe ion complex (TA-Fe3+) are successfully prepared. Among them, the wood-based solar water evaporator with 3 mm zebra stripes exhibits excellent photothermal water evaporation performance, achieving a water evaporation rate of 1.44 kg·m−2·h−1 under the illumination intensity of one sun. Its water evaporation performance is significantly superior to that of other coating patterns, proving that the bionic design of zebra patterns is effective and can improve water evaporation efficiency. This work provides new insights into the development of safe and environmentally friendly solar interfacial water evaporation materials through bionic design.